2019
DOI: 10.1177/0266242619889527
|View full text |Cite
|
Sign up to set email alerts
|

Identity work in entrepreneurship education: Activating, scripting and resisting the entrepreneurial self

Abstract: Entrepreneurship education (EE) theory and practice show increasing interest in the concept of identity work as integral to entrepreneurial learning. EE offers various approaches to guiding students towards entrepreneurial identities, but critics note that these meet neoliberal manifestations of the entrepreneurial self, leaving little room for alternative identities to be cultivated in EE. Concerned with this critique, we aim to contribute to the EE literature through a detailed investigation of the identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 75 publications
0
39
0
1
Order By: Relevance
“…Hytti and Heinonen (2013), for instance, in their study of gendered identity construction through EE, found that CE “acted as an emancipatory tool” (p. 894) allowing female participants to construct an alternative, more authentic, “humane” entrepreneurial identity, free of the “heroic”(which was relatively easily accepted by the male students). Frederiksen and Berglund (2020) propose new “rules” for teacher-student interactions, to ensure that alternative identities can be cultivated (rather than the reproduction of traditional, neoliberal notions of entrepreneurship). Donnellon et al (2014) emphasize the importance of active learning through entrepreneurship, (as opposed to education that is conducted about, in or for entrepreneurship); and they identify four main methods of facilitating entrepreneurial identity construction: socialization and collectivity, strategic positioning, visual and oral symbols and storytelling.…”
Section: Discussionmentioning
confidence: 99%
“…Hytti and Heinonen (2013), for instance, in their study of gendered identity construction through EE, found that CE “acted as an emancipatory tool” (p. 894) allowing female participants to construct an alternative, more authentic, “humane” entrepreneurial identity, free of the “heroic”(which was relatively easily accepted by the male students). Frederiksen and Berglund (2020) propose new “rules” for teacher-student interactions, to ensure that alternative identities can be cultivated (rather than the reproduction of traditional, neoliberal notions of entrepreneurship). Donnellon et al (2014) emphasize the importance of active learning through entrepreneurship, (as opposed to education that is conducted about, in or for entrepreneurship); and they identify four main methods of facilitating entrepreneurial identity construction: socialization and collectivity, strategic positioning, visual and oral symbols and storytelling.…”
Section: Discussionmentioning
confidence: 99%
“…Entrepreneurship education as a space for identity work (Frederiksen & Berglund, 2020) has been raised as important, but future research could approach this more from the intersectionality perspective, including understanding of gender, race, ethnicity, and class. Research on academic entrepreneurship could benefit from understanding the different visible or invisible barriers or boundaries that exist for the 'universal right to entrepreneurship' that is currently used as a mantra in academic entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have acknowledged how "creating an entrepreneurial identity" may lead to a governing of young people to fit the neoliberal market society as well (Berglund, 2013;Hytti & Heinonen, 2013;Siivonen et al, 2019). EE is not merely about improving participants' knowledge base or offering enterprising skills, but also an arena of identity work in shaping students' identities and subjecting them to identity regulation (Hedeboe Frederiksen & Berglund, 2020). It may be easier to detect efforts to turn students into entrepreneurs than to discern the processes of fostering students as entrepreneurial selves who fit the needs of late capitalism (Berglund et al, 2017).…”
Section: Ee As a Domain For Identity Workmentioning
confidence: 99%
“…It may be easier to detect efforts to turn students into entrepreneurs than to discern the processes of fostering students as entrepreneurial selves who fit the needs of late capitalism (Berglund et al, 2017). Although this subject position is difficult to detect-and therefore to resist-students have recently circumvented it through compliance or truth-telling strategies (Hedeboe Frederiksen & Berglund, 2020). Zawadzki et al (2020) illustrate the struggles involved in resisting neoliberal demands and the efforts needed to affirm an ethical reorientation of the entrepreneurial self in management studies.…”
Section: Ee As a Domain For Identity Workmentioning
confidence: 99%